2002
DOI: 10.5650/jos.51.615
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Distribution of Highly Unsaturated Fatty Acids in Triacylglycerols of Artemia Nauplii Enriched with Marine Oils.

Abstract: Brine shrimp Artemia nauplii, an important live food used in aquaculture, were enriched with five marine oil triacylglycerols (TAG) in order to enhance n-3 highly unsaturated fatty acids (HUFA) essential for fish larvae. Positional distribution of fatty acids in TAG was determined for both of the enriched Artemia nauplii and dietary marine oils. In all of the enriched Artemia nauplii, docosahexaenoic acid was preferentially located in the sn-1,3 position followed by the sn-2 position. Icosapentaenoic acid was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…This result agrees with recent studies in the regiospecific analysis of fish oil triacylglycerols 19,20 .…”
Section: Fish Oil Samplessupporting
confidence: 93%
“…This result agrees with recent studies in the regiospecific analysis of fish oil triacylglycerols 19,20 .…”
Section: Fish Oil Samplessupporting
confidence: 93%
“…Moreover, changes in the positional distribution of FA of dietary TAG were also observed in Artemia nauplii enriched with fish oil ethyl esters and TAG (Ando and Narukawa, 2002;Ando and Oomi, 2001;Ando et al, 2004;Shiozaki and Ando, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Table A Table A.2, it can be observed that docosahexaenoic acid is mostly found at sn-2 position. This result agrees with recent studies in the regiospecific analysis of fish oil triacylglycerols (Ando & Narukawa 2002;Jayasinghe et al 2012).…”
Section: Sardine Oil Samplessupporting
confidence: 93%